Tribocorrosion behavior of TiO2/Al2O3 nanolaminate, Al2O3, and TiO2 thin films produced by atomic layer deposition - Radi, Polyana Alves; Testoni, Giorgio Ernesto; Pessoa, Rodrigo Sávio; Maciel, Homero Santiago; Rocha, Luís Augusto [UNESP]; Vieira, Lucia (Elsevier, 2018)
Metallic materials are the most widely used for orthopedic applications and, their corrosion resistance is one of the main prerequisites for avoiding impairment of the material properties due to degradation. Ti-6Al-4V is one of the main medical titanium alloys. However, for permanent implant applications, this alloy may cause toxic effect due to release of vanadium and aluminum. Nanolaminates of alternatively ordered thin films of transition metal oxides with nanoscale thickness are known to have distinct properties of a single layer film. Atomic layer deposition (ALD) is a promising method for fabrication of thin sealing coatings for corrosion protection. These films can also be used as in vivo sensors to antedate the detection of diseases such as cancer, to inform the best treatments, and to understand the response to therapies. The ideal in vivo sensor should be non-toxic, biocompatible, stable, and very sensitive. In this work, TiO2/Al2O3 nanolaminate, Al2O3 and TiO2 thin films were deposited on Ti-6Al-4V substrates by using ALD and their structure, adhesion and tribocorrosion properties were analyzed. The tribocorrosion tests were performed in Ringer's solution. The coatings showed to protect the sample surface evidenced by the increase on the OCP both in static mode and in dynamic mode. The TiO2/Al2O3 nanolaminates presented lower friction coefficient.
Keywords: Al2O3; ALD; Nanolaminates; TiO2; Tribocorrosion; Tribology